1988
DOI: 10.1111/j.1600-0528.1988.tb01852.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary levels of Streptococcus mutans and lactobacilli and dental caries experiences in a US adolescent population

Abstract: Dental caries exams and saliva samples were obtained from 541 adolescents, aged 10-15, initially and after 17 months as part of a 3-yr longitudinal study investigating the relationships of dietary intakes, specific microorganisms in saliva, and the prevalence and incidence of dental caries. The mean DMFS score detected in these subjects initially was 4.61, and they developed an average of 1.38 new DMFS during the first 17-month period. Initially, S. mutans and lactobacilli were detected in 64% and 56% of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 21 publications
3
49
1
5
Order By: Relevance
“…A placa bacteriana desempenha papel essencial no desenvolvimento da cárie e certos agentes estão mais freqüentemente envolvidos. Estudos em jovens não-diabéticos mostraram que aqueles com níveis baixos de estreptococos mutans e lactobacilos apresentavam menor número de cáries (26)(27)(28)(29)(30). No entanto, nos jovens diabéticos, esta relação não é clara (19,20,31), e a comparação da quantificação destas bactérias entre portadores ou não da doença também não é conclusiva (12)(13)(14)(15).…”
Section: Discussionunclassified
“…A placa bacteriana desempenha papel essencial no desenvolvimento da cárie e certos agentes estão mais freqüentemente envolvidos. Estudos em jovens não-diabéticos mostraram que aqueles com níveis baixos de estreptococos mutans e lactobacilos apresentavam menor número de cáries (26)(27)(28)(29)(30). No entanto, nos jovens diabéticos, esta relação não é clara (19,20,31), e a comparação da quantificação destas bactérias entre portadores ou não da doença também não é conclusiva (12)(13)(14)(15).…”
Section: Discussionunclassified
“…A 17-month longitudinal study (Kingman et al, 1988) 11 of 541 US adolescents initially aged 10-15 years was conducted with a view to using the child's baseline level of lactobacilli in saliva as a screening test for children at high risk of developing caries. A bacterial level of lactobacilli >10 5 was regarded as a positive test result and this was compared with the child's caries increment after 17 months, where at least three new lesions in the period were recorded as a positive disease result.…”
Section: Diagnostic and Screening Testsmentioning
confidence: 99%
“…Forest plots presenting estimates of sensitivity and specificity and corresponding 95% CI of salivary mutans streptococci with thresholds from >100 to >1 000 000 CFU/ml. Forest plots based on data presented in the study by Kingman et al, (1988). Referencestandard (caries increment) thresholds were DMFS >0, DMFS >1, DMFS >2 for each index test threshold value of CFU/ml, in ascending order.…”
Section: Diagnostic Accuracy Of Methods To Identify Individuals With mentioning
confidence: 99%
“…It is unclear whether mutans streptococci were identified by their characteristic CFU-morphology as no study reported criteria for this. In only two studies (Petti & Hausen, 2000;Kingman et al, 1988) the growth of mutans streptococci was confirmed by biochemical testing. Figure 8 presents recruited, withdrawn, and included adolescents in study IV.…”
mentioning
confidence: 98%
See 1 more Smart Citation